2018
DOI: 10.1186/s12872-018-0912-3
|View full text |Cite
|
Sign up to set email alerts
|

Coronary calcium score improves the estimation for pretest probability of obstructive coronary artery disease and avoids unnecessary testing in individuals at low extreme of traditional risk factor burden: validation and comparison of CONFIRM score and genders extended model

Abstract: BackgroundReliability of models for estimating pretest probability (PTP) of obstructive coronary artery disease (CAD) has not been investigated in individuals at low extreme of traditional risk factor (RF) burden. Thus, we sought to validate and compare CONFIRM score and Genders extended model (GEM) among these individuals.MethodsWe identified symptomatic individuals with 0 or 1 RF who underwent coronary calcium scan and coronary computed tomographic angiography (CCTA). Follow-up clinical data were also record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In summary, women admitted to a CPU were less often diagnosed with a coronary diagnosis than men with a leading noncoronary diagnosis being a hypertensive crisis. This confirms findings of the WISE and WISE-CVD studies in which higher rates of endothelial and microvascular dysfunction as noncoronary reasons and the CONFIRM study where lower rates of obstructive CVD in women have been reported [23-25]. Nearly half of the male patients (46.7%) and about two thirds of female patients (66.2%) of all patients presenting to a CPU with suspected ACS were found to have non-ACS diagnoses, underlining the importance of accessibility of a wide-spread diagnostic workup within the hospital, especially in female patients.…”
Section: Discussionsupporting
confidence: 86%
“…In summary, women admitted to a CPU were less often diagnosed with a coronary diagnosis than men with a leading noncoronary diagnosis being a hypertensive crisis. This confirms findings of the WISE and WISE-CVD studies in which higher rates of endothelial and microvascular dysfunction as noncoronary reasons and the CONFIRM study where lower rates of obstructive CVD in women have been reported [23-25]. Nearly half of the male patients (46.7%) and about two thirds of female patients (66.2%) of all patients presenting to a CPU with suspected ACS were found to have non-ACS diagnoses, underlining the importance of accessibility of a wide-spread diagnostic workup within the hospital, especially in female patients.…”
Section: Discussionsupporting
confidence: 86%
“…Comparing patients discharged alive with patients who died, the median (lower-upper quartiles) age was 65 y/o (56-76) vs 77 y/o (72-82), (p<0.001), n=95 (56%) vs n=74 (68%) were males, p=0.061, dyslipidemia was present in n=29 (17%) vs n=30 (28%), p=0.052, n=15 (9) vs n=26 (24), p=0.001 had prior cardiovascular disease, D-dimer median was 723 ng/ml (lower-upper quartile, 495-1119) vs 1.083 ng/ml (lower-upper quartile, 704-2248), p<0.001, CRP median 78.15 mg/L (lower-upper quartile, 36.8-132.5) vs 148.3 mg/L (lower-upper quartile, 91-209.4), p<0.001, median CCS was 17 (lower-upper quartile, 0-248) vs 188.7 (lower-upper quartile, 20.3-671.6), p<0.001 and the PCAT attenuation median was −76.4 HU (lower-upper quartile, −79.3, −76.6) vs - 68.6 HU (lower-upper quartile, −75.9, −63.3), p<0.001. Figure 3 graphically shows the distribution of age, main laboratory and imaging variables according to the in-hospital outcome.…”
Section: Resultsmentioning
confidence: 99%
“…We aimed to investigate whether the Agatston coronary calcium score (CCS), which correlates with coronary artery disease (CAD) (9), or peri-coronary adipose tissue (PCAT) attenuation, which correlates with coronary inflammation (10), are associated with higher mortality in COVID-19 patients, independently from other risk factors and extent of lung disease. Both parameters can be measured in HRCT scans, although only CCS has been previously measured in non-contrast, non ECG-triggered HRCT scans (11).…”
Section: Introductionmentioning
confidence: 99%
“…42 The substantially steady results of the CONFIRM score on several data-sets are also confirmed on a validation data-set consisting of subjects at the low extreme of traditional cardiovascular risk factor burden. 51…”
Section: Validated Ptp Models: Main Resultsmentioning
confidence: 99%
“…42 The substantially steady results of the CONFIRM score on several data-sets are also confirmed on a validation data-set consisting of subjects at the low extreme of traditional cardiovascular risk factor burden. 51 The Corus® CAD model stands out from the previous ones because it defines an ageand sex-specific gene expression score. Validation is performed by AUC comparisons, HL test and additivity to DFM and other models.…”
Section: Predictive Variables and Discrimination Capabilitymentioning
confidence: 99%